(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
Nowadays social networks are a way of expressing themselves; few people have had them, however that ended up changing, and nowadays they have become a requirement, being used even by companies and becoming a competitive differential. The objective of the study is to analyze how social networks influence the behavior and buying attitude of university students from a public and a private institution. It was carried out by means of a bibliographic research and, regarding the methodology used, it is considered a quantitative study, by means of non- probabilistic sampling and by quotas in two higher education institutions, one public and the other private, with 100 university students. The main findings indicate that 70% of academics agree that social networks facilitate contact with the product; likewise, 70% consider it important that companies have social networks. On the other hand, 49% agree that social networks influence the time of purchase; and for 47% the stores offer sales facilities through them. Although, for 29% of academics, the security offered by social networks has only 29% approval, and only 15% believe that the quality of the product is the same as described on social networks. Finally, among the most used social networks for purchase are Whatsapp (48%), followed by Facebook (34%) and, lastly, Instagram (14%). As a contribution, it was possible to understand the behavior of academics, which is a young and more connected audience, what can help organizations create specific strategies according to the characteristics of this group.